Does transition from an unstable labour market position to permanent employment protect mental health? Results from a 14-year follow-up of school-leavers - Hammarström Anne; Novo Mehmed; Reine Ieva (BMC, 2008)
Abstract Background Having secure employment, in contrast to being unemployed, is regarded as an important determinant of health. Research and theories about the negative health consequences of unemployment indicated that transition from unemployment to a paid job could lead to improved health. The objective of this study was to test the hypothesis that obtaining permanent employment after being in an unstable labour market position protects mental health. Methods A 14-year follow-up of all graduates from compulsory school in an industrial town in northern Sweden was performed at ages 16, 18, 21 and 30 years. Complete data on the cohort were collected for 1044 individuals with the aid of a comprehensive questionnaire. The response rate was 96.4%. The health measurement used in this study was the psychological symptoms analysed by multivariate logistic regression. Those who obtained permanent employment were the focus of the analysis. This group consisted of people who were in an unstable labour market position for a year or more between the ages of 25 and 29, and who had acquired a permanent job one year before and at the time of the investigation. Results After controlling for gender as well as for an indicator of health-related selection, possible confounders and mediators, an association was found between the lower probability of psychological symptoms and obtaining permanent employment (OR = 0.35, 95% CI 0.19-0.63) as well as having permanent employment (OR = 0.22, 95% CI 0.10-0.51). Conclusion Our findings suggest that transition from an unstable labour market position to permanent employment could be health-promoting, even after controlling for possible confounders and mediators, as well as for an indicator of health-related selection. However, as there are few studies in the field, there is a need for more longitudinal studies in order to further analyse the relationship and to examine possible explanations. The policy implication of our study is that the transformation of unstable labour market positions into permanent employment could contribute to better public health.